Desenvolvimento de uma escala em silicone para tons de pele humana - Neves, Ana Christina Claro [UNESP] (1996)
The objective of this paper was to develop one silicone guide for human skin shades. Twenty-seven samples were manufactured in acetic silicone rubber (Silastic 732 RTV) pigmented with iron oxides and titanium dioxide. The qua ntity of acetic silicone rubber used in each specimen was kept constant (two grams) and the pigments were mixed to it in several proportions until the obtention of twenty-seven different shades. Through the comparison of the color of each sample with the skin color of forty-one individuals were selected the five samples which shades best matched the individuals' skin colar, determining in this way, a shade guide. Variations in the quantity of pigments used permited the obtention of new shades. With the employed methodology it was possible to develop a shade guide that can facilitate the definition of the patient's skin color when making facial prostheses in silicone allowing economy of time and material at the moment of color selection